TextWorld: A Learning Environment for Text-based Games - Côté, Marc-Alexandre; Kádár, Ákos; Yuan, Xingdi; Kybartas, Ben; Barnes, Tavian; Fine, Emery; Moore, James; Hausknecht, Matthew; El Asri, Layla; Adada, Mahmoud; Tay, Wendy; Trischler, Adam (Computer Games Workshop at ICML/IJCAI 2018, 2018)
We introduce TextWorld, a sandbox learning environment for the training and evaluation of RL agents on text-based games. TextWorld is a Python library that handles interactive playthrough of text games, as well as backend functions like state tracking and reward assignment. It comes with a curated list of games whose features and challenges we have analyzed. More signiﬁcantly, it enables users to handcraft or automatically generate new games. Its generative mechanisms give precise control over the diﬃculty, scope, and language of constructed games, and can be used to relax challenges inherent to commercial text games like partial observability and sparse rewards. By generating sets of varied but similar games, TextWorld can also be used to study generalization and transfer learning. We cast text-based games in the Reinforcement Learning formalism, use our framework to develop a set of benchmark games, and evaluate several baseline agents on this set and the curated list.